Le Rôle De L’intégration Des Supply Chains Dans La Performance Du Secteur Agroalimentaire : Cas DuMaroc - Hamri, Mohammed Hicham; Ouariti, Ouafae Zerouali; Lechheb, Hafsa (European Scientific Journal, ESJ, 2017)
The integration of Supply Chains can be considered as the level at which a firm can strategically collaborate with the links in its Supply Chain, in order to realize product and service flows on the market, and to satisfy the aspirations of customers with the least Costs. The purpose of this paper is to analyze in theory the relevance of taking into account the integration of Supply Chains in the performance of the agri-food sector, particularly in Morocco, while trying to answer the following question: What is the impact of the integration of Supply Chains on the performance of the Moroccan agri-food sector?